Suppressor of MEK null (SMEK)/protein phosphatase 4 catalytic subunit (PP4C) is a key regulator of hepatic gluconeogenesis - Yoon, Young-Sil (National Academy of Sciences, 2010)
Fasting promotes hepatic gluconeogenesis to maintain glucose homeostasis. The cAMP-response element binding protein (CREB)-regulated transcriptional coactivator 2 (CRTC2) is responsible for transcriptional activation of gluconeogenic genes and is critical for conveying the opposing hormonal signals of glucagon and insulin in the liver. Here, we show that suppressor of MEK null 1 (SMEK1) and SMEK2 [protein phosphatase 4 (PP4) regulatory subunits 3a and 3b, respectively] are directly involved in the regulation of hepatic glucose metabolism in mice. Expression of hepatic SMEK1/2 is up-regulated during fasting or in mouse models of insulin-resistant conditions in a Peroxisome Proliferator-Activated Receptor-gamma Coactivator 1α (PGC-1α)-dependent manner. Overexpression of SMEK promotes elevations in plasma glucose with increased hepatic gluconeogenic gene expression, whereas depletion of the SMEK proteins reduces hyperglycemia and enhances CRTC2 phosphorylation; the effect is blunted by S171A CRTC2, which is refractory to salt-inducible kinase (SIK)-dependent inhibition. Taken together, we would propose that mammalian SMEK/PP4C proteins are involved in the regulation of hepatic glucose metabolism through dephosphorylation of CRTC2.